2020
DOI: 10.1002/dvdy.147
|View full text |Cite
|
Sign up to set email alerts
|

Modeling ocular lens disease in Xenopus

Abstract: Background: Ocular lens clouding is termed as cataract, which depending on the onset, is classified as congenital or age-related. Developing new cataract treatments requires new models. Thus far, Xenopus embryos have not been evaluated as a system for studying cataract. Results: We characterized the developmental process of lens formation in Xenopus laevis tailbuds and tadpoles, and we disrupted the orthologues of three mammalian cataract-linked genes in F0 by CRISPR/Cas9. We assessed the consequences of gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
(72 reference statements)
0
16
0
Order By: Relevance
“…In step 2, we examined the effects of varying the amount of Cas9 mRNA per embryo, as it has been shown that increasing the Cas9 mRNA amount to a certain level improves gene disruption efficiency in X. tropicalis (Blitz et al, 2013; Nakayama et al, 2013). Although previous studies have cultured injected embryos at various temperatures ranging from 12 to 22°C, there are no reports examining the effects of varying the culture temperature while keeping all other experimental conditions constant (Banach et al, 2017; Carr et al, 2021; Feehan et al, 2017; Kato et al, 2021; Smith et al, 2020; Tsujioka et al, 2017: Viet et al, 2020). Therefore, in step 3, we examined the effects of varying the embryo culture temperature post injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In step 2, we examined the effects of varying the amount of Cas9 mRNA per embryo, as it has been shown that increasing the Cas9 mRNA amount to a certain level improves gene disruption efficiency in X. tropicalis (Blitz et al, 2013; Nakayama et al, 2013). Although previous studies have cultured injected embryos at various temperatures ranging from 12 to 22°C, there are no reports examining the effects of varying the culture temperature while keeping all other experimental conditions constant (Banach et al, 2017; Carr et al, 2021; Feehan et al, 2017; Kato et al, 2021; Smith et al, 2020; Tsujioka et al, 2017: Viet et al, 2020). Therefore, in step 3, we examined the effects of varying the embryo culture temperature post injection.…”
Section: Introductionmentioning
confidence: 99%
“…Clustered regulatory interspaced short palindromic repeats/CRISPR associated protein 9 (CRISPR/Cas9) has become a popular genome editing tool in Xenopus laevis (Aslan et al, 2017; Banach et al, 2017; Bharathan & Dickinson, 2019; Carr et al, 2021; Delay et al, 2018; Delay et al, 2019; Ezawa et al, 2021; Feehan et al, 2017; Jaffe et al, 2016; Kato et al, 2021; Kim et al, 2021; Ledford et al, 2017; Martin et al, 2020; Naert et al, 2020; Ochi et al, 2017; Pickett et al, 2017; Smith et al, 2020; Square et al, 2020; Tandon et al, 2017; Tsujioka et al, 2017; Viet et al, 2020; Wang et al, 2015; Wen et al, 2019; Wyatt et al, 2021). Importantly, most studies to date delivered the CRISPR reagents using a microinjection into fertilized eggs.…”
Section: Introductionmentioning
confidence: 99%
“…The main abnormities of the frog lens are shown in Figure 1. The picture of abnormities in the lenses of both eyes is often symmetrical; most likely, these are genotypic changes in the lens, and not acquired abnormities as a result of environmental contamination (Viet et al, 2020). Such changes account for about 12% of all abnormities.…”
Section: Resultsmentioning
confidence: 99%
“…Not all of these have fully documented the underlying DNA sequence variation at the DSB site. Some did use next generation sequencing (NGS) [12][13][14] or Sanger sequencing of cloned genomic isolates from the embryos [14][15][16][17][18][19]. Others merely monitored the breakdown of Sanger traces from directly amplified DNA at the target site, combined with a deconvolution algorithm to predict likely repairs [20,21].…”
Section: Published Xenopus Crispr/cas9 Research -Can the Mosaicism That Results From Repair Of Cas9 Dsbs Be Eliminated?mentioning
confidence: 99%